Sistem Diagnosa Penyakit Autis pada Anak dengan Metode Forward Chaining Berbasis Web - Mutasar, Novia Hasdyna (Jurnal Elektronika dan Teknologi Informasi, 2023)
The increasing number of children with autism in the world makes autism, which was previously not too much of a problem by parents, becoming increasingly known and feared. The rapid increase in the number of people with autism is not proportional to the number of professionals studying this field. This often causes confusion in making the diagnosis. The purpose of this research is to apply the forward chaining method and certainty factor into a web-based application that can diagnose autism in children in real time. The results of this study can provide information about the diagnosis of autism in children and can see medical records that are easily understood by the public.